Memorandum of understanding between Universiti Teknologi MARA and Universitas Jenderal Achmad Yani Indonesia - Mohd Mokhtar, Mohd Amin (Faculty of Medicine, 2023)
On the 2nd of March 2023, The Faculty of Medicine, Universiti Teknologi MARA (UiTM), and the Universitas Jenderal Achmad Yani (UNJANI) signed the Memorandum of Understanding (MoU) on cooperation in the field of learning, research and publication. UiTM was represented by the Vice Chancellor, Professor Datuk Ts. Dr Hajah Roziah Mohd Janor while the witness was Professor Dr Fazah Akhtar Hanapiah, the Dean of Faculty of Medicine UiTM.